The effectiveness of meditation techniques to overcome music performance anxiety among students of Faculty Music UiTM Shah Alam / Muhammad Saufi Nasyari - Nasyari, Muhammad Saufi (Faculty of Music, 2012)
This study was carried out in January 2011 - January 2012 in the Faculty of Music, Universiti Teknologi Mara, Shah Alam. The scope of study focused on Degree music students during for this semester. This study was initiated based on problems and feedback from the students regarding feeling of nervous and anxious during their performance and poor performance in the forum and performance classes. The main objectives of this study were: 1) To gather the method to overcome performance anxiety 2) To understand how the method function 3) To identify whether the method works with the student. A survey questionnaire (Jun 2010) had been distributed directly to the music students in various places in the university to getting know the current situation of anxiety, then a meditation treatment were conducted which takes times of five weeks followed by interview on selective respondents in the faculty based on their belief in ability to change, responsibility, and attitude toward this technique since this can influence the treatment outcome (Smith, 1976: Benson, 1978: Franks, 1963). From the survey most of the students are facing their anxiety more during the performance rather than before and after a performance. Findings from the interview showed that meditation were beneficial in order to overcome anxiety problem for students in the Faculty of Music UiTM Shah Alam. Feeling calmer, relax, confidence and focus were reported which it was several effects of meditation. Unconsciously, it was also proved that by doing several methods that divided into two groups which was physical such as exercise, warm up, walking around, eat a banana or chocolate and non-physical such as scream out loud before the performance, talk to the person ones belief was not so effective to reduce anxiety compared to meditation.